Comparison of Continuous positive airway pressure versus High flow nasal cannula for Oral feeding Preterm infants (CHOmP): randomized pilot study. (4th March 2022) - Leibel, Sandra L.; Castro, Marina; McBride, Tammy; Hassall, Kelly; Sarmiento, Karla; Ye, Xiang Y.; Shah, Vibhuti
Abstract: Objective: To assess the feasibility of conducting a study comparing nasal continuous positive airway pressure (nCPAP) or heated, humidified, high flow nasal cannula (HHHFNC) on oral feeding in preterm infants. Study design: Randomized controlled pilot study in a level III NICU, of infants' born ≤28° /7  weeks who at 34° /7  weeks post menstrual age (PMA) were dependent on noninvasive ventilation (NIV). Infants were randomized evenly to nCPAP or HHHFNC groups and orally fed on low-flow oxygen. The primary outcomes of enrollment and retention were assessed. Results: We enrolled 40 infants and 12 completed the study in the nCPAP group versus 13 in the HHHFNC group. Using our respiratory and feeding protocols, we showed overall enrollment and retention rates (95%CI) at 0.66 (0.54, 0.77) and 0.63 (0.48, 0.78), respectively. Breastfeeding rates were 82% in the nCPAP group and 76% in the HHHFNC group. Infants in the HHHFNC group reached full feeds 7 days earlier than those in the nCPAP group Conclusions: Based on our retention rate, an adequately powered randomized controlled trial can be performed to confirm or refute that HHHFNC is associated with achieving oral feeds earlier. Trial registration: United States National Library of Medicine (www.clinicaltrials.gov ) Identifier: NCT02055339. First posted 2/5/2014.